Effects of thinner compliant electrodes on self-clearability of dielectric elastomer actuators - Lau, Gih-Keong (2021)
A metalized plastic capacitor stands a higher chance to clear faults when embodied with thinner electrodes. However, it is not clear whether the same thickness effect applies to carbon-based compliant electrodes in clearing the defects in dielectric elastomer actuators (DEA). This experimental study showed that charcoal-powder compliant electrodes act like fuses and current limiters to successfully clear the defects of an acrylic dielectric elastomer actuator, provided a very thin electrode coating. For example, DEAs with 3 μm thick (average) charcoal-powder electrodes fast cleared faults and sustained high breakdown strength (300 to 400 MV/m), but the ones with thicker charcoal-powder electrodes (30 μm thick on average) succumbed to persisting breakdowns in a weaker electric field (200 to 300 MV/m). Thermo-gravitational analysis and differential scanning calorimetry showed that dielectric elastomer (3M VHB F9473PC) started to ignite at 350 ∘C, and charcoal powders (Mungyo charcoal pastel MP-12CP) started burning above 450 ∘C. This confirmed that flash ignition and its damping of charcoal powder is possible only with a very thin electrode coating relative to acrylic elastomer substrate thickness. Too thick of a charcoal-powder coating could lead to the spread of burning beyond the initial flash point, and incomplete burning that punctures the dielectric layer but shorts across opposite electrodes. With this insight, one can design self-clearable electrodes to improve the dielectric strength of dielectric elastomer actuators.